Hazard Classification Of Gamat – N,N-Diethyl-M-Toluamide (DEET) Mosquito Repellent Cream Using The United Nations Globally Harmonized System (UN-GHS) Based On Rats Acute Dermal Toxicity - Ramli, Norhidayah (2015)
The study is aimed to identify clinical signs exhibited by rats upon single exposure of Gamat – N,N-diethyl-m-toluamide (DEET) Mosquito Repellent Cream (GDMRC) containing 15 percent of N,N-diethyl-m-toluamide as the active ingredient with bioactivity (repellent) against mosquitoes which includes Gamat Cream (GC) as the placebo item. The study is performed to determine the hazard category of acute dermal toxicity of the GDMRC subsequently to classify it based on the WHO Pesticide Hazard Class and the UN-GHS harmonized classification of hazardous chemical substances.